BRACKISH WATER DESALINATION IN SUNGAI ITIK AREA USING REVERSE OSMOSIS (RO) METHOD - Setiawan, Eric; Danial, Mochammad Meddy; Purnaini, Rizki; Soeryamassoeka, S. B. (Jurnal Teknik Sipil, 2024)
This research addresses the complexities of treating brackish and seawater from Sungai Itik using Reverse Osmosis (RO), emphasizing advanced pre-treatment methods, hybrid RO systems, and fouling control. Pilot-scale tests confirmed the feasibility of these approaches in meeting clean water standards and balancing economic and environmental sustainability.Using a single ultra-low pressure (ULP) RO membrane, salinity decreased by 57.36%, Total Dissolved Solids (TDS) by 25.76%, and watercolor by 63.25%, achieving improved water quality. Expanding to a ULP and Brackish Water (BW) membrane combination further reduced salinity by 40.63%, TDS by 35.76%, and watercolor by 92.13%, highlighting the benefits of hybrid systems for varied water conditions. In seawater treatment, a ULP membrane reduced salinity by 69.48%, TDS by 93.49%, and watercolor by 97.74%, proving effective for converting seawater to potable or industrial-grade water. Combining ULP and BW membranes achieved salinity reductions of 94.67%, TDS by 94.02%, and watercolor by 34.94%, which is crucial for applications needing ultra-clean water. These findings underscore RO's potential to mitigate water quality challenges and support sustainable water management in diverse environments.